2014
DOI: 10.1038/nn.3869
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of fear learning and memory in distributed neuronal circuits

Abstract: How sensory information is transformed by learning into adaptive behaviors is a fundamental question in neuroscience. Studies of auditory fear conditioning have revealed much about the formation and expression of emotional memories and have provided important insights into this question. Classical work focused on the amygdala as a central structure for fear conditioning. Recent advances, however, have identified new circuits and neural coding strategies mediating fear learning and the expression of fear behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
371
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(383 citation statements)
references
References 119 publications
(167 reference statements)
10
371
1
1
Order By: Relevance
“…The activity of BLA neurons is not exclusively shaped by sensory input, however; principal neurons and interneurons in the BLA have been shown to receive monosynaptic input from mPFC and vHPC, and send reciprocal projections to both of these regions [66][67][68] . Activity within these pathways can both directly invigorate the anxiety response (e.g., through projections of the vHPC to the lateral septum and hypothalamic nuclei; see below), as well as influence the likelihood of a threat appraisal (e.g., through fear memory retrieval via mPFC projections to the amygdala; see below, and 69 ).…”
Section: Interpreting Threats On the Macrocircuit Levelmentioning
confidence: 99%
“…The activity of BLA neurons is not exclusively shaped by sensory input, however; principal neurons and interneurons in the BLA have been shown to receive monosynaptic input from mPFC and vHPC, and send reciprocal projections to both of these regions [66][67][68] . Activity within these pathways can both directly invigorate the anxiety response (e.g., through projections of the vHPC to the lateral septum and hypothalamic nuclei; see below), as well as influence the likelihood of a threat appraisal (e.g., through fear memory retrieval via mPFC projections to the amygdala; see below, and 69 ).…”
Section: Interpreting Threats On the Macrocircuit Levelmentioning
confidence: 99%
“…From a neurobiological perspective, a pivotal mechanism for transforming threat into adaptive behaviors is Pavlovian fear conditioning, a form of associative learning that allows to predict aversive events (Herry and Johansen, 2014). Experimentally, Pavlovian fear conditioning is established by repeatedly coupling a neutral stimulus (CS+) with an aversive stimulus (UCS), which leads to a conditioned response (CR) to the CS+ alone (Sehlmeyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of intranasally delivered exogenous OXT (OXT IN ) have shown that the peptide produces anxiolytic-like effects as a result of dampened amygdala reactivity to threat (Eckstein and Hurlemann, 2013;Domes et al, 2007, but see Lischke et al, 2012), thereby promoting in-group trust (Kosfeld et al, 2005), cooperation (De Dreu et al, 2010) and affiliative behaviors (Hurlemann and Scheele, 2015;Rilling and Young, 2014). The amygdala-an ensemble of functionally distinct nuclei located in the medial temporal lobe-is central to a distributed neural circuitry orchestrating Pavlovian fear conditioning in humans and other species, underscoring its crucial role in promoting reproductive fitness (Herry and Johansen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pavlovian auditory threat (fear) conditioning (23, 24) is a form of associative learning during which a neutral auditory conditioned stimulus (CS) is temporally paired with an aversive unconditioned stimulus (US), often a mild electric shock (17,20,21,(25)(26)(27). Following training, the auditory CS comes to elicit behavioral defense responses (such as freezing) and supporting physiological changes controlled by the autonomic nervous and endocrine systems.…”
mentioning
confidence: 99%